Higher Serum Uric Acid Is Associated with Higher Bone Mineral Density in Chinese Men with Type 2 Diabetes Mellitus - Dian-dian Zhao; Pei-lin Jiao; Jing-jia Yu; Xiao-jing Wang; Lin Zhao; Yan Xuan; Li-hao Sun; Bei Tao; Wei-qing Wang; Guang Ning; Jian-min Liu; Hong-yan Zhao (International Journal of Endocrinology)
Accumulating evidence suggests that oxidative stress is associated with osteoporosis. Serum uric acid (UA) is a strong endogenous antioxidant. Therefore, we investigated the relationship between the serum UA and BMD in Chinese men with T2DM. In this cross-sectional study of 621 men with T2DM, BMDs at lumbar spine (L2–4), femoral neck (FN), and total hip (TH) were measured by dual-energy X-ray absorptiometry (DXA). Serum levels of UA, calcium (Ca), 25-OH vitamin D3 (vitD3), parathyroid hormone (PTH), and creatinine (Cr) were also tested. Data analyses revealed that serum UA levels were positively associated with BMD at all sites (p<0.05) in men with T2DM after adjusting for multiple confounders. The serum UA levels were positively correlated with body weight (r=0.322), body mass index (BMI) (r=0.331), Ca (r=0.179), and Cr (r=0.239) (p<0.001) and were also positively associated with the concentrations of PTH (r=0.10, p<0.05). When compared with those in the lowest tertile of UA levels, men with T2DM in the highest tertile had a lower prevalence of osteoporosis or osteopenia (adjusted odds ratio 0.54, 95% confidence interval [CI] 0.31–0.95). These data suggest that higher serum levels of UA are associated with higher BMDs and lower risks of osteoporosis in Chinese men with T2DM.